Monitoring of SARS-CoV-2 RNA in wastewater as an epidemiological surveillance tool in Mendoza, Argentina - Giraud Billoud, Maximiliano German (2021)
Wastewater-based epidemiology (WBE) is an emerging tool that gives temporal and spatial information on a population's health status. Here, we report the epidemiological dynamics of a population of ~1.2 million residents in the metropolitan region of Mendoza province, Argentina, within the period July 2020 to January 2021. We combined the use of WBE of two wastewater treatment plants with epidemiological surveillance of the corresponding populations. We applied two viral concentration methods (polyethylene glycol precipitation and aluminum-based adsorption-flocculation) and RNA isolation methods in each wastewater sample to increase the possibility of detection and quantification of nucleocapsid markers (N1 and N2) of SARS-CoV-2 by RT-qPCR. Overall, our results allowed us to trace the rise, exponential growth, plateau, and fall of SARS-CoV-2 infections for 26 weeks. Individual analysis for each wastewater treatment plant showed a positive correlation between the viral load of SARS-CoV-2 genetic markers and COVID-19 cases that were diagnosed per week. Our findings indicate that WBE is a useful epidemiological indicator to anticipate the increase in COVID-19 cases and monitor the advance of the pandemic and different waves of infections.